Environment-friendly vinyl silicone oil and preparation method thereof

By coating the magnetic core material with organic matter and loading it into a porous support of hydroxyapatite, a magnetic catalyst is prepared that is easy to recover and does not interfere with the preparation reaction of vinyl silicone oil, which solves the problem of compact coating and recycling of magnetic materials in the prior art, and achieves efficient and environmentally friendly vinyl silicone oil production.

CN119570035AInactive Publication Date: 2025-03-07ZHEJIANG ZHENGHE SILICONE MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411959474.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve dense coating of magnetic materials, especially for porous materials, which is conflicting with the need to increase the specific surface area and porosity of the carrier, and the transition metal iron element in the magnetic materials can interfere with the ring-opening balance reaction of vinyl silicone oil.

Method used

Magnetic core material containing cationic polymers and coated the surface with organic matter containing anionic polymers to form magnetic particles. These magnetic particles are then supported in a porous support of hydroxyapatite to form a solid catalyst with magnetic responsive characteristics to facilitate recovery and avoid contact of magnetic materials with the reaction system.

Benefits of technology

It realizes convenient recycling and recycling of catalysts, avoids interference with magnetic materials on the preparation reaction of vinyl silicone oil, improves reaction efficiency and yield, reduces production costs, and improves the environmental friendliness of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides environment-friendly vinyl silicone oil and a preparation method thereof, and belongs to the technical field of material chemistry. The preparation method of the environment-friendly vinyl silicone oil comprises the following steps: feeding cyclic polysiloxane and an end-capping reagent into a reaction device, and heating and dehydrating under inert gas protection and vacuum conditions; adding a solid catalyst into the reaction device, and heating for reaction; adjusting substances in the reaction device to be neutral, and performing reduced pressure distillation to remove low-boiling-point substances to obtain vinyl silicone oil; the solid catalyst is prepared by the following steps: preparing a magnetic core material; coating the surface of the magnetic core material to obtain magnetic particles; preparing a porous carrier from a raw material comprising magnetic particles; and loading the catalyst on a porous carrier to obtain the solid catalyst. According to the method, the catalyst which is good in catalytic effect and convenient to recycle and recycle is adopted, so that the environment-friendly degree of vinyl silicone oil production is improved, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material chemistry, and in particular to an environmentally friendly vinyl silicone oil and a preparation method thereof. Background Art

[0002] Vinyl silicone oil is the main raw material for preparing liquid silicone rubber, silicone gel and other products. Vinyl silicone oil mainly includes vinyl-terminated polydimethylsiloxane and vinyl-terminated polymethylvinylsiloxane. Among them, vinyl-terminated polydimethylsiloxane is usually obtained by using dimethylsiloxane ring body or octamethylcyclotetrasiloxane as raw material, vinyl siloxane as end-capping agent, and ring-opening equilibrium reaction using alkaline catalyst.

[0003] The prior art related to the preparation of vinyl silicone oil generally uses porous materials loaded with organic bases or inorganic bases as solid catalysts. The prior art requires such solid catalysts to have a high specific surface area and a three-dimensional interconnected pore structure, and a high density of active sites. High-density active sites can increase the reaction rate, and high specific surface area can provide a suitable spatial structure for the diffusion of reactants and the conduct of the reaction. In addition, the solid catalyst also needs to be easy to recycle and recycle. Solid catalysts that meet the above conditions help to increase the rate and yield of the reaction, reduce production costs, and improve the environmental friendliness in the production process.

[0004] Porous solid catalysts in powder or granular form usually have a large specific surface area and a high mass transfer rate, and therefore have a high catalytic activity. In order to facilitate the recovery of powder or granular solid catalysts, the prior art chooses to impart magnetic response properties to the solid catalyst by loading a magnetic material containing iron elements, so as to separate the solid catalyst from the reaction system.

[0005] For example, the Chinese patent with the authorization announcement number CN113663710B provides a method for preparing a magnetic solid acid catalyst, and the Chinese patent with the authorization announcement number CN114100634B provides a method for preparing a magnetic multi-component catalyst.

[0006] From the above analysis, it can be seen that powdered or granular porous solid catalysts that can be separated and recovered using magnetic response characteristics have many technical advantages. However, the shortcomings of the prior art including the above patent documents are that the prior art can only achieve the co-compounding of magnetic materials and catalysts in carrier materials, but it is difficult to achieve dense coating of magnetic materials. Especially for porous materials, the demand for dense coating of magnetic materials is contradictory to the demand for increasing the specific surface area and porosity of the carrier.

[0007] Although the addition of magnetic materials has no effect on some reaction systems, for the preparation process of vinyl silicone oil, the transition metal iron element contained in the magnetic material will interfere with the ring-opening equilibrium reaction of vinyl silicone oil.

[0008] Therefore, how to use magnetic materials to improve the recovery convenience of powdered or granular porous solid catalysts, avoid exposure of magnetic materials to the reaction system to affect the ring-opening equilibrium reaction required for the preparation of vinyl silicone oil, and ensure the reaction yield is a technical problem that technicians in this field need to solve. Summary of the invention

[0009] One of the problems solved by the present invention is how to provide a catalyst for the production of vinyl silicone oil that is easy to recycle, so as to improve the environmental friendliness of the production of vinyl silicone oil, ensure its reaction efficiency and yield, and reduce its production cost.

[0010] In order to solve at least one of the above problems, the present invention provides a method for preparing an environmentally friendly vinyl silicone oil, the preparation method comprising: S110, feeding the cyclic polysiloxane and the end-capping agent into a reaction device, and heating and dehydrating the cyclic polysiloxane under inert gas protection and vacuum conditions; S120, adding a solid catalyst to the reaction device and heating the reaction; S130, adjusting the substances in the reaction device to be neutral, and performing reduced pressure distillation to remove low-boiling point substances to obtain vinyl silicone oil; Wherein, the solid catalyst is prepared by the following steps: S210, preparing a magnetic core material containing a cationic polymer; S220, coating the surface of the magnetic core material with an organic substance containing anionic polymer to obtain magnetic particles; S230, preparing a hydroxyapatite porous carrier using raw materials including magnetic particles; S240, loading the catalyst onto a hydroxyapatite porous carrier to obtain an alkaline solid catalyst.

[0011] In any of the above technical solutions, the mass ratio of solid catalyst: end-capping agent: cyclic polysiloxane is (0.5-2): (2-6): 100; and / or the cyclic polysiloxane is a dimethylsiloxane ring or octamethylcyclotetrasiloxane; and / or the end-capping agent is vinylcyclosiloxane or tetramethyldivinylsiloxane.

[0012] In any of the above technical solutions, in S110, the vacuum condition is -0.2MPa to -0.05MPa; and / or in S110, the temperature of heating and dehydration is 65°C to 75°C, and the time of heating and dehydration is 60min to 100min.

[0013] In any of the above technical solutions, in S120, the temperature of the heating reaction is 100° C. to 110° C.; and / or in S120, the time of the heating reaction is 2.5 h to 3.5 h.

[0014] In any of the above technical solutions, in S130, the pressure condition of the reduced pressure distillation is -0.2 MPa to -0.05 MPa; and / or in S130, the temperature condition of the reduced pressure distillation is 180°C to 200°C.

[0015] In any of the above technical solutions, S210 specifically includes: S211, adding citric acid and ethanol into water in a mass ratio of aminopropyl triethoxysilane: chitosan: citric acid: ferric nitrate: ethanol: water = (1-2): (2-4): (8-10): (30-35): (25-30): 100 and mixing evenly, adding aminopropyl triethoxysilane, chitosan and ferric nitrate and mixing evenly again, adding concentrated nitric acid dropwise and stirring until chitosan is completely dissolved to obtain an iron salt solution; S212, mixing 1,4-diaminobenzene in ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding sodium hydroxide and water and mixing again to obtain an alkaline solution; S213, adding alkaline solution to the iron salt solution and stirring continuously until the pH value is 10-11, after the addition is completed, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain iron sol; S214. The iron sol is fed into a reactor and subjected to a hydrothermal treatment for 2.5 to 3 hours at a pressure of 3 MPa to 5 MPa and a temperature of 180°C to 190°C. After the hydrothermal treatment, the solid matter is separated and filtered, washed, and dried to obtain a magnetic core material.

[0016] In any of the above technical solutions, S220 specifically includes: S221, 1,4-benzenedicarboxaldehyde, 2-acrylamide-2-methyl-propanesulfonic acid, 2-hydroxyethyl acrylate, acrylic acid and water are uniformly mixed in a mass ratio of ammonium persulfate: 1,4-benzenedicarboxaldehyde: 2-acrylamide-2-methyl-propanesulfonic acid: 2-hydroxyethyl acrylate: acrylic acid: magnetic core material: water = (0.2-0.3): (0.4-1.2): (2-3): (4-6): (6-8): (20-25): 100, and ammonium persulfate and the magnetic core material are added and mixed again to obtain a first mixture; S222, heating the first mixture to 80° C. to 90° C., and irradiating the first mixture with ultraviolet light for 1 h to 1.5 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223. After the ultraviolet light irradiation treatment is completed, the solid matter is separated and filtered, washed, and dried to obtain magnetic particles.

[0017] In any of the above technical solutions, S230 specifically includes: S231, mixing sodium hexametaphosphate, magnetic particles, calcium nitrate and water in a mass ratio of sodium hexametaphosphate: magnetic particles: calcium nitrate: water = (0.2-0.4): (10-15): (25-35): 100 to obtain a second mixture; S232. Heat the second mixture to 55 to 65°C, add an aqueous solution of dipotassium hydrogen phosphate to the second mixture at a molar ratio of calcium to phosphorus of 1.67:1, and simultaneously keep warm and stir. Continue stirring for 3 to 4 hours after the addition is complete. After stirring, adjust the pH value to 10 to 11, send it into a reactor, and perform hydrothermal treatment at a pressure of 0.8 to 1.6 MPa and a temperature of 115 to 125°C for 8 to 10 hours. After the hydrothermal treatment is completed, separate and filter the solids, wash, and dry to obtain a porous carrier.

[0018] In any of the above technical solutions, S240 specifically includes: S241. Add the porous carrier to a mixture of inorganic base and water in a mass ratio of porous carrier: inorganic base: water = (20-50): (20-50): 100. Mix and dry to constant weight, then place in a muffle furnace and heat treat at a temperature of 120° C. to 140° C. for 4 to 6 hours to obtain a solid catalyst.

[0019] The present invention also provides an environmentally friendly vinyl silicone oil, which is obtained by using the preparation method of any of the above technical solutions.

[0020] Beneficial Effects The present invention provides a method for preparing an environmentally friendly vinyl silicone oil. The preparation method uses cyclic polysiloxane and a capping agent as raw materials, first vacuum dehydrates the two, and then adds a catalyst to make the above raw materials undergo a ring-opening equilibrium reaction to obtain vinyl silicone oil. For the purpose of reducing the production cost of vinyl silicone oil and improving the environmental friendliness of its production process, the present invention adopts a solid catalyst to promote and catalyze the above reaction. In order to facilitate the recovery and recycling of the solid catalyst, the present invention prepares a catalyst with magnetic response characteristics, and by coating an organic film layer on the surface of the magnetic response material, the magnetic response material is prevented from contacting the reaction system and interfering with the reaction. Through electrostatic adsorption, the film layer containing anionic polymers is uniformly and densely coated on the surface of the magnetic core material containing cationic polymers. In addition, the present invention loads the coated magnetic response material and catalyst on a hydroxyapatite porous carrier, and uses the characteristics of the porous carrier having a high specific surface area and rich pore structure to load the magnetic response material and catalyst, thereby ensuring the catalytic activity, reaction efficiency, and the convenience of catalyst recovery. The hydroxyapatite porous carrier can maintain good mechanical strength and chemical stability in an alkaline environment and is a good alkaline catalyst carrier. Therefore, the present invention improves the environmental friendliness of the vinyl silicone oil preparation process and reduces its production cost by adopting an improved solid catalyst. DETAILED DESCRIPTION

[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention. Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.

[0022] The present invention provides a method for preparing vinyl silicone oil, which comprises: S110, feeding the cyclic polysiloxane and the end-capping agent into a reaction device, and heating and dehydrating the cyclic polysiloxane under inert gas protection and vacuum conditions; S120, adding a solid catalyst to the reaction device and heating the reaction; S130, adjusting the substances in the reaction device to be neutral, and performing reduced pressure distillation to remove low-boiling point substances to obtain vinyl silicone oil.

[0023] In the above steps, the cyclic polysiloxane is specifically dimethylsiloxane ring body or octamethylcyclotetrasiloxane. The end-capping agent is specifically vinylcyclosiloxane or tetramethyldivinylsiloxane. Wherein, by mass ratio, solid catalyst: end-capping agent: cyclic polysiloxane = (0.5-2): (2-6): 100. Preferably, by mass ratio, solid catalyst: end-capping agent: cyclic polysiloxane = (0.6-1.2): (2-2.5): 100.

[0024] The reaction device used in S110 is specifically a reactor. Before the heating reaction, the raw materials need to be vacuum dehydrated. The vacuum dehydration is carried out in an inert gas protection atmosphere such as nitrogen or argon. The vacuum condition is specifically -0.2MPa to -0.05Mpa, preferably -0.08MPa to -0.05Mpa. The temperature condition used for vacuum dehydration is 65°C to 75°C, and the heating dehydration time is 60min to 100min.

[0025] The purpose of S120 is to drive the ring-opening equilibrium reaction by adding a catalyst and heating. The heating reaction temperature of S120 is 100° C. to 110° C., and the heating reaction time is 2.5 h to 3.5 h.

[0026] After the ring-opening equilibrium reaction is completed, the reaction needs to be terminated by adjusting the reaction system to neutrality, and vacuum distillation is performed to remove low-boiling substances. The pressure condition of the vacuum distillation is -0.2MPa to -0.05MPa, and the temperature condition of the vacuum distillation is 180°C to 200°C.

[0027] Through the above steps, vinyl silicone oil can be obtained. The present invention uses a porous solid catalyst to promote the reaction. In order to facilitate the recovery and recycling of the catalyst used in the above reaction, the present invention loads the magnetic response material in the porous solid catalyst. In order to avoid contact between the magnetic response material and the reaction system, the present invention carries out an organic coating treatment on the magnetic core material that exerts the magnetic response effect. Thus, a catalyst that is easy to recycle and has good catalytic activity can be obtained, thereby improving the environmental friendliness of the production of vinyl silicone oil and reducing its production cost.

[0028] Specifically, the solid catalyst of the present invention is prepared by the following steps: S210, preparing a magnetic core material containing a cationic polymer; S220, coating the surface of the magnetic core material with an organic substance containing anionic polymer to obtain magnetic particles; S230, preparing a hydroxyapatite porous carrier using raw materials including magnetic particles; S240, loading the catalyst onto a hydroxyapatite porous carrier to obtain an alkaline solid catalyst.

[0029] In the above steps, powder or particles of ferric oxide and / or ferrosoferric oxide can be used as the magnetic core material. The magnetic core material can be obtained by commercial purchase, or by using raw materials such as ferric nitrate or ferric sulfate, such as sol-gel method, hydrothermal method, etc. It can be understood that the nanoscale magnetic core material with uniform particle size distribution prepared by sol-gel method, hydrothermal method, etc. has good magnetic response performance and is a preferred embodiment of the present invention.

[0030] In some implementations of the present invention, S210 specifically includes: S211, according to the mass ratio of aminopropyl triethoxysilane: chitosan: citric acid: ferric nitrate: ethanol: water = (1-2): (2-4): (8-10): (30-35): (25-30): 100, add citric acid and ethanol into water and mix evenly, add aminopropyl triethoxysilane, chitosan and ferric nitrate and mix evenly again, add 68wt% concentrated nitric acid dropwise and stir until chitosan is completely dissolved to obtain an iron salt solution; S212, mixing 1,4-diaminobenzene in ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding sodium hydroxide and water and mixing again to obtain an alkaline solution; S213, adding alkaline solution to the iron salt solution and stirring continuously until the pH value is 10-11, after the addition is completed, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain iron sol; S214. The iron sol is fed into a reactor and subjected to a hydrothermal treatment for 2.5 to 3 hours at a pressure of 3 MPa to 5 MPa and a temperature of 180°C to 190°C. After the hydrothermal treatment, the solid matter is separated and filtered, washed, and dried to obtain a magnetic core material.

[0031] In the above steps, S211 uses water-soluble iron nitrate to prepare an iron salt solution with ethanol and water as a mixed solvent. Among them, aminopropyl triethoxysilane is used as a silane coupling agent to reduce the surface energy of the magnetic core material formed subsequently and enhance its coupling with organic matter. Chitosan is used as a cationic modifier to enhance the tightness and uniformity of the connection between the magnetic core material and organic matter. In an alkaline environment, the iron ions in the iron salt solution combine with hydroxyls to form iron hydroxide colloid. The purpose of S212 is to prepare an alkaline solution for reacting with the iron salt solution. It should be noted that alkaline solutions such as sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and ammonia water can all be used to react with the iron salt solution. The present invention selects a mixed solution of ethanol and water of sodium hydroxide, and adds 1,4-diaminobenzene to the sodium hydroxide aqueous solution. The purpose of using ethanol in S212 is to dissolve the weakly alkaline 1,4-diaminobenzene so that it can be evenly dispersed in the mixture of ethanol and water. The purpose of S213 is to prepare an iron hydroxide sol containing chitosan and 1,4-diaminobenzene. After obtaining the above sol, the present invention chooses to convert iron hydroxide into iron oxide by hydrothermal method under heating and pressure conditions. It can be understood that heat treatment above 500°C can also achieve the conversion of iron hydroxide into iron oxide, but in order to protect chitosan and 1,4-diaminobenzene, the present invention chooses hydrothermal treatment not exceeding 200°C. In summary, through the above steps, iron oxide doped with chitosan and 1,4-diaminobenzene can be obtained, and the present invention uses this as a magnetic core material.

[0032] The purpose of S220 is to coat the surface of the magnetic core material with organic matter to avoid contact between the magnetic core material and the reaction system of vinyl silicone oil. It can be understood that a uniform, dense and thin film layer is a preferred embodiment of the present invention. In order to obtain a uniform and dense organic film layer, the magnetic core material can be coated with an organic polymer, or an organic monomer can be mixed with the magnetic core material and the coating can be achieved by initiating a polymerization reaction.

[0033] In some implementations of the present invention, S220 specifically includes: S221, 1,4-benzenedicarboxaldehyde, 2-acrylamide-2-methyl-propanesulfonic acid, 2-hydroxyethyl acrylate, acrylic acid and water are uniformly mixed in a mass ratio of ammonium persulfate: 1,4-benzenedicarboxaldehyde: 2-acrylamide-2-methyl-propanesulfonic acid: 2-hydroxyethyl acrylate: acrylic acid: magnetic core material: water = (0.2-0.3): (0.4-1.2): (2-3): (4-6): (6-8): (20-25): 100, and ammonium persulfate and the magnetic core material are added and mixed again to obtain a first mixture; S222, heating the first mixture to 80° C. to 90° C., and irradiating the first mixture with ultraviolet light for 1 h to 1.5 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223. After the ultraviolet light irradiation treatment is completed, the solid matter is separated and filtered, washed, and dried to obtain magnetic particles.

[0034] In the above steps, the purpose of S221 is to mix the ammonium persulfate initiator, 2-acrylamide-2-methyl-propanesulfonic acid having a sulfonic acid group, and 2-hydroxyethyl acrylic acid ester monomer with the magnetic core material in a water-soluble solvent system of acrylic acid and water to obtain a first mixture in a suspended state. Under heating conditions of 80°C to 90°C, the above organic monomers undergo a polymerization reaction, and the negatively charged sulfonic acid groups and hydroxyl groups in the above organic matter chemically adsorb with the chitosan dopant having cationic characteristics in the magnetic core material, thereby making the polymer uniformly coated on the surface of the magnetic core material. In addition, the sulfonic acid group in the 2-acrylamide-2-methyl-propanesulfonic acid of the sulfonic acid group generates free radicals under ultraviolet light irradiation, thereby catalyzing the condensation reaction of the amino group of 1,4-diaminobenzene in the magnetic core material with the aldehyde group of 1,4-benzenedicarboxylic acid to form an imide group. The imide group with good stability can realize the chemical bond between iron oxide and organic matter, improve the uniformity and density of organic coating on the magnetic core material, and improve the chemical stability and thermal stability of the organic film layer, ensuring that under the conditions of ring-opening equilibrium reaction for preparing vinyl silicone oil, the organic film layer on the surface of the magnetic core material will not be destroyed, thereby avoiding contact between the magnetic core material and the reaction system.

[0035] The purpose of S230 is to load the magnetic particles on a porous carrier. It is understood that porous inorganic materials such as porous ceramics, attapulgite, montmorillonite, hydroxyapatite, halloysite, zeolite, silica aerogel, etc. can all be used as solid catalyst carriers. The way to load the magnetic particles on the porous carrier can be to mechanically mix the magnetic particles with the porous carrier and granulate and then sinter, or to deposit or fill the magnetic particles in the pores of the porous carrier by ultrasound, stirring, wet chemistry, etc. in the liquid phase.

[0036] In some implementations of the present invention, S230 specifically includes: S231, mixing sodium hexametaphosphate, magnetic particles, calcium nitrate and water in a mass ratio of sodium hexametaphosphate: magnetic particles: calcium nitrate: water = (0.2-0.4): (10-15): (25-35): 100 to obtain a second mixture; S232. Heat the second mixture to 55 to 65°C, add an aqueous solution of dipotassium hydrogen phosphate to the second mixture at a molar ratio of calcium to phosphorus of 1.67:1, and simultaneously keep warm and stir. Continue stirring for 3 to 4 hours after the addition is complete. After stirring, adjust the pH value to 10 to 11, send it into a reactor, and perform hydrothermal treatment at a pressure of 0.8 to 1.6 MPa and a temperature of 115 to 125°C for 8 to 10 hours. After the hydrothermal treatment is completed, separate and filter the solids, wash, and dry to obtain a porous carrier.

[0037] In the above steps, the purpose of S231 is to use sodium hexametaphosphate as a dispersant to evenly disperse the magnetic particles in water-soluble calcium nitrate to obtain a suspended magnetic particle calcium nitrate suspension. Calcium nitrate is used as a calcium source and an aqueous solution of dipotassium hydrogen phosphate is used as a phosphorus source. The two are mixed according to a specific calcium-phosphorus ratio and the pH value is adjusted to be alkaline to obtain porous hydroxyapatite. Thus, the above steps can obtain a hydroxyapatite porous carrier evenly loaded with magnetic particles.

[0038] The purpose of S240 is to load the catalyst onto the hydroxyapatite porous carrier containing magnetic particles. The catalyst used in the present invention is preferably an alkaline catalyst, which can be an inorganic base such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc., or an organic base can be selected.

[0039] In some implementations of the present invention, S240 specifically includes: S241. Add the porous carrier to a mixture of inorganic base and water in a mass ratio of porous carrier: inorganic base: water = (20-50): (20-50): 100. Mix and dry to constant weight, then place in a muffle furnace and heat treat at a temperature of 120° C. to 140° C. for 4 to 6 hours to obtain a solid catalyst.

[0040] In the above steps, an inorganic alkaline substance is used as a catalyst, which is loaded on a hydroxyapatite porous carrier containing magnetic particles as a catalyst for driving the catalytic ring-opening equilibrium reaction in the preparation process of vinyl silicone oil. Wherein, the inorganic base can specifically be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide, barium hydroxide, barium oxide, calcium oxide, and magnesium oxide. Preferably, the inorganic base is sodium hydroxide. Wherein, on the basis of adding an inorganic base, an organic base with a mass of 5wt% to 25wt% of the inorganic base can also be added in S241. The organic base can specifically be selected from dodecyl trimethyl ammonium chloride, trimethyl benzyl ammonium chloride, tetramethyl ammonium chloride, tetramethyl ammonium bromide, tetramethyl ammonium hydroxide, tetraethyl ammonium hydroxide, tetrapropyl ammonium hydroxide, tetrabutyl ammonium hydroxide, tetramethyl ammonium hydroxide, etc. Preferably, the organic base is dodecyl trimethyl ammonium chloride.

[0041] Embodiment 1 In this embodiment, a series of solid catalyst samples were prepared, and the raw material ratios thereof were shown in Table 1. The preparation process thereof was as follows: S1. Add citric acid and anhydrous ethanol into a beaker filled with deionized water and mix well. Add KH550 aminopropyl triethoxysilane, chitosan and ferric nitrate and mix well again. Slowly drop 68% concentrated nitric acid and stir magnetically at a speed of 180 rpm / min until chitosan is completely dissolved to obtain an iron salt solution. S2. Mix 1,4-diaminobenzene evenly in a beaker filled with anhydrous ethanol, add deionized water mixed with sodium hydroxide, and mix again to obtain an alkaline solution; S3, slowly adding alkaline solution to the iron salt solution and continuously stirring the solution with magnetic stirring at a speed of 180 rpm / min until the pH value is 11, and after the addition is completed, continuously stirring the solution with magnetic stirring at a temperature of 90° C. and evaporating the solution in a water bath to obtain iron sol; S4, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours under a pressure of 3.4 MPa and a temperature of 185° C., after the hydrothermal treatment, separating and filtering the solids, washing with water once, and drying with hot air at 110° C. to obtain a magnetic core material; S5, 1,4-benzenedicarboxaldehyde, 2-acrylamide-2-methyl-propanesulfonic acid, 2-hydroxyethyl acrylate, acrylic acid and deionized water are mixed in a beaker, ammonium persulfate and magnetic core material are added and mixed again, and ultrasonic homogenization is performed at a power of 400 W for 30 minutes to obtain a first mixture; S6, heating the first mixture to 85° C., continuously stirring with magnetic force at a speed of 400 rpm / min and keeping warm, and simultaneously using an ultraviolet light source with a wavelength of 254 nm and a power of 800 W to irradiate the first mixture with ultraviolet light for 1 hour; S7, separating and filtering the solids, washing with acetone twice, washing with water twice, and drying with hot air at 110° C. to obtain magnetic particles; S8, mixing calcium nitrate and deionized water in a beaker, adding sodium hexametaphosphate and magnetic particles, mixing again, and performing ultrasonic dispersion treatment at a power of 400 W for 10 min to obtain a second mixture; S9, heating the second mixture to 60°C, adding 18wt% of an aqueous solution of dipotassium hydrogen phosphate to the second mixture at a calcium-phosphorus molar ratio of 1.67:1, and simultaneously keeping warm and stirring, continuing magnetic stirring at a speed of 300rpm / min for 3h after the addition is completed, adjusting the pH value to 11 after the stirring is completed, sending it into a reactor, and hydrothermally treating it at a pressure of 1.2Mpa and a temperature of 120°C for 8h. After the hydrothermal treatment is completed, separating and filtering the solids, washing with water twice, and drying with hot air at 110°C to obtain a porous carrier; S10, adding the porous carrier to an aqueous solution of sodium hydroxide, drying to constant weight, sending it into a muffle furnace, and performing heat treatment at a temperature of 135° C. for 6 hours to obtain a solid catalyst.

[0042] Table 1 Comparative Example 1 In this comparative example, a solid catalyst sample 5 was prepared, and its raw material ratio is shown in Table 2. Its preparation process is as follows: S1. Add citric acid and anhydrous ethanol into a beaker filled with deionized water and mix well. Add KH550 aminopropyl triethoxysilane, chitosan and ferric nitrate and mix well again. Slowly drop concentrated nitric acid and stir magnetically at a speed of 180 rpm / min until chitosan is completely dissolved to obtain an iron salt solution. S2, mixing sodium hydroxide and deionized water to prepare an 8wt% alkaline solution; S3, slowly adding alkaline solution to the iron salt solution and continuously stirring the solution with magnetic stirring at a speed of 180 rpm / min until the pH value is 11, and after the addition is completed, continuously stirring the solution with magnetic stirring at a temperature of 90° C. and evaporating the solution in a water bath to obtain iron sol; S4, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours under a pressure of 3.4 MPa and a temperature of 185° C., after the hydrothermal treatment, separating and filtering the solids, washing with water once, and drying with hot air at 110° C. to obtain a magnetic core material; S5, 2-acrylamide-2-methyl-propanesulfonic acid, 2-hydroxyethyl acrylate, acrylic acid and deionized water are mixed uniformly in a beaker, ammonium persulfate and magnetic core material are added and mixed again, and ultrasonic homogenization is performed at a power of 400 W for 30 minutes to obtain a first mixture; S6, heating the first mixture to 85° C., stirring the mixture with magnetic force at a speed of 400 rpm / min and keeping the temperature for 1 h; S7 to S10 are the same as those in the first embodiment.

[0043] Table 2 Comparative Example 2 In this comparative example, a solid catalyst sample 6 was prepared, and its raw material ratio was the same as that of sample 1 in Example 1, and its preparation process was as follows: S1 to S5 are the same as in Embodiment 1; S6, heating the first mixture to 85° C., stirring the mixture with magnetic force at a speed of 400 rpm / min and keeping the temperature for 1 h; S7 to S10 are the same as those in the first embodiment.

[0044] Embodiment 2 In this embodiment, a series of vinyl silicone oil samples were prepared, and the raw material ratios thereof were shown in Table 3. The preparation process thereof was as follows: S1. Feed the cyclic polysiloxane and the end-capping agent into a reaction device, and heat and dehydrate at 70°C for 80 minutes under nitrogen protection and a vacuum condition of -0.05Mpa; S2, adding a solid catalyst to the reaction device, and heating to 105°C for 3h; S3. Recover the solid catalyst, adjust the pH value of the substance in the reaction device to 7, and perform reduced pressure distillation at a pressure of -0.08 MPa and a temperature of 180° C. to remove low-boiling point substances to obtain vinyl silicone oil.

[0045] The performance test parameters of the vinyl silicone oil sample prepared in this example are shown in Table 3.

[0046] Table 3 Accelerated testing In order to measure the recycling performance of the catalyst, the present invention further implements an accelerated test, and the test method of the accelerated test is as follows: S1. Solid catalyst samples 1 to 6 are mixed with the vinyl cyclosiloxane and dimethyl cyclosiloxane ring body which have been vacuum dehydrated in the manner of Example 2, respectively, at a mass ratio of solid catalyst: vinyl cyclosiloxane: dimethyl cyclosiloxane ring body = 1.5:5:100, to obtain mixture samples 1 to 6 in sequence; S2, respectively reacting the mixture samples 1 to 6 under nitrogen protection and a temperature of 105° C. for 3 hours; S3, after the reaction is completed, the solid catalyst is recovered by magnetic separation, and the same solid catalyst sample is used to repeat the above reaction steps S1 and S2 20 times; S4. For the last reaction in the cyclic execution step of S3 above, the yield of vinyl silicone oil in this reaction was tested. The test results are shown in Table 4.

[0047] Table 4 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing an environmentally friendly vinyl silicone oil, characterized in that: The preparation method comprises: S110, feeding the cyclic polysiloxane and the end-capping agent into a reaction device, and heating and dehydrating the cyclic polysiloxane under inert gas protection and vacuum conditions; S120, adding a solid catalyst to the reaction device and heating the reaction; S130, adjusting the substances in the reaction device to be neutral, and performing reduced pressure distillation to remove low-boiling point substances to obtain the vinyl silicone oil; Wherein, the solid catalyst is prepared by the following steps: S210, preparing a magnetic core material containing a cationic polymer; S220, coating the surface of the magnetic core material with an organic substance containing anionic polymer to obtain magnetic particles; S230, using a raw material including the magnetic particles to prepare a hydroxyapatite porous carrier; S240, loading the catalyst onto the hydroxyapatite porous carrier to obtain the alkaline solid catalyst.

2. The preparation method according to claim 1, characterized in that: In terms of mass ratio, solid catalyst: end-capping agent: cyclic polysiloxane = (0.5-2): (2-6): 100; and / or The cyclic polysiloxane is a dimethylsiloxane ring or an octamethylcyclotetrasiloxane; and / or The end-capping agent is vinyl cyclosiloxane or tetramethyl divinyl siloxane.

3. The preparation method according to claim 1, characterized in that: In S110, the vacuum condition is -0.2 MPa to -0.05 MPa; and / or In S110, the temperature of the heating and dehydration is 65° C. to 75° C., and the time of the heating and dehydration is 60 min to 100 min.

4. The preparation method according to claim 1, characterized in that: In S120, the temperature of the heating reaction is 100° C. to 110° C.; and / or In S120, the heating reaction time is 2.5 hours to 3.5 hours.

5. The preparation method according to claim 1, characterized in that: In S130, the pressure condition of the reduced pressure distillation is -0.2 MPa to -0.05 MPa; and / or In S130, the temperature condition of the reduced pressure distillation is 180°C to 200°C.

6. The preparation method according to any one of claims 1 to 5, characterized in that S210 specifically includes: S211, adding the citric acid and the ethanol to the water in a mass ratio of aminopropyl triethoxysilane:chitosan:citric acid:ferric nitrate:ethanol:water=(1-2):(2-4):(8-10):(30-35):(25-30):100 and mixing evenly, adding the aminopropyl triethoxysilane, the chitosan and the ferric nitrate and mixing evenly again, adding concentrated nitric acid dropwise and stirring until the chitosan is completely dissolved, thereby obtaining an iron salt solution; S212, mixing the 1,4-diaminobenzene in the ethanol in a mass ratio of 1,4-diaminobenzene: sodium hydroxide: ethanol: water = (2-4): (8-10): (10-20): 100, adding the sodium hydroxide and the water and mixing again to obtain an alkaline solution; S213, adding the alkaline solution dropwise to the iron salt solution and continuously stirring until the pH value is 10-11, after the addition is completed, stirring the iron salt solution at a temperature of 85° C. to 95° C. and evaporating in a water bath to obtain an iron sol; S214, sending the iron sol into a reactor, and performing a hydrothermal treatment for 2.5 hours to 3 hours under a pressure condition of 3Mpa to 5Mpa and a temperature condition of 180°C to 190°C. After the hydrothermal treatment, separating and filtering the solids, washing, and drying to obtain the magnetic core material.

7. The preparation method according to claim 6, characterized in that: S220 specifically includes: S221, the 1,4-benzenedicarboxaldehyde, the 2-acrylamide-2-methyl-propanesulfonic acid, the 2-hydroxyethyl acrylate, the acrylic acid and the water are uniformly mixed in a mass ratio of ammonium persulfate: 1,4-benzenedicarboxaldehyde: 2-acrylamide-2-methyl-propanesulfonic acid: 2-hydroxyethyl acrylate: acrylic acid: magnetic core material: water = (0.2-0.3): (0.4-1.2): (2-3): (4-6): (6-8): (20-25): 100, and the ammonium persulfate and the magnetic core material are added and mixed again to obtain a first mixture; S222, heating the first mixture to 80° C. to 90° C., and irradiating the first mixture with ultraviolet light for 1 h to 1.5 h using an ultraviolet light source with a wavelength of 254 nm to 365 nm and a power of 600 W to 800 W under simultaneous stirring and heat preservation; S223, after the ultraviolet light irradiation treatment is completed, the solid matter is separated and filtered, washed, and dried to obtain the magnetic particles.

8. The preparation method according to claim 7, characterized in that: S230 specifically includes: S231, mixing the sodium hexametaphosphate, the magnetic particles, the calcium nitrate and the water in a mass ratio of sodium hexametaphosphate: magnetic particles: calcium nitrate: water = (0.2-0.4): (10-15): (25-35): 100 to obtain a second mixture; S232, heat the second mixture to 55°C to 65°C, add an aqueous solution of dipotassium hydrogen phosphate to the second mixture at a molar ratio of calcium to phosphorus of 1.67:1, and simultaneously keep warm and stir, continue stirring for 3h to 4h after the addition is complete, adjust the pH value to 10 to 11 after stirring, send it into a reactor, and hydrothermally treat it at a pressure of 0.8Mpa to 1.6Mpa and a temperature of 115°C to 125°C for 8h to 10h. After the hydrothermal treatment is completed, separate and filter the solids, wash, and dry to obtain the porous carrier.

9. The preparation method according to claim 8, characterized in that: S240 specifically includes: S241. Add the porous carrier to a mixture of the inorganic base and the water in a mass ratio of porous carrier: inorganic base: water = (20-50): (20-50): 100, mix and dry to constant weight, then put into a muffle furnace, and perform heat treatment at a temperature of 120° C. to 140° C. for 4 h to 6 h to obtain the solid catalyst.

10. An environmentally friendly vinyl silicone oil, characterized in that: The environmentally friendly vinyl silicone oil is obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A magnetic solid acid catalyst and its application in the catalytic fructose hydrolysis reaction

    CN113663710B

  • Preparation method, product and application of a magnetic multi-component iron-carbon composite Fenton catalyst

    CN114100634B

  • Loading type Pd base metal nanometer cluster catalyst, preparing method and applications thereof

    CN101767018A

  • Method for preparing carbon coating magnetism halloysite adsorbent by utilizing humic acid and obtained product thereof

    CN108514863A

  • Method for catalytically preparing polysiloxane through supported phosphonitrile catalyst

    CN110358090A